2015
DOI: 10.1148/radiol.14141237
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Combined Digital Mammography and Tomosynthesis Screening for Women with Dense Breasts

Abstract: Purpose To evaluate the comparative effectiveness of combined biennial digital mammography and tomosynthesis screening, compared to biennial digital mammography screening alone, among women with dense breasts. Materials and Methods We used an established, discrete-event breast cancer simulation model to estimate the comparative clinical effectiveness and cost-effectiveness of biennial screening with both digital mammography and tomosynthesis versus digital mammography alone among U.S. women ages 50–74 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 30 publications
1
81
0
1
Order By: Relevance
“…Therefore, this assumption may have caused our study to underestimate the benefits of screening. Ideally, one would use an established microsimulation model such as those used as part of NCI's Cancer Intervention Surveillance Network (CISNET) project to estimate the life expectancies for women undergoing screening more accurately (38)(39)(40). However, there is no such validated model that uses primary data of Turkish female population; therefore, we leave this for future research.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this assumption may have caused our study to underestimate the benefits of screening. Ideally, one would use an established microsimulation model such as those used as part of NCI's Cancer Intervention Surveillance Network (CISNET) project to estimate the life expectancies for women undergoing screening more accurately (38)(39)(40). However, there is no such validated model that uses primary data of Turkish female population; therefore, we leave this for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Lee et al, 26 simulation models of breast cancer were utilized. Compared with biennial FFDM alone, the researchers showed that combined biennial FFDM and digital breast tomosynthesis for US women aged 50 to 74 years with dense breasts would avert 1 additional breast cancerrelated death per 2,000 women screened as well as 405 false-positive findings on screening examinations per 1,000 women.…”
Section: Screening Mammography and Tomosynthesismentioning
confidence: 99%
“…Compared with biennial FFDM alone, the researchers showed that combined biennial FFDM and digital breast tomosynthesis for US women aged 50 to 74 years with dense breasts would avert 1 additional breast cancerrelated death per 2,000 women screened as well as 405 false-positive findings on screening examinations per 1,000 women. 26 They concluded that adding tomosynthesis to biennial FFDM for women aged 50 to 74 years with dense breasts was likely to improve health outcomes at a reasonable cost. 26 Thus, the evidence supports the finding that digital breast tomosynthesis improves detection rates of breast cancer with both increased sensitivity and specificity.…”
Section: Screening Mammography and Tomosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In the interim, the three-dimensional reconstruction technology of digital breast tomosynthesis was approved by Health Canada (in 2009, but is limited in availability) and by the U.S. Food and Drug Administration [but only as an adjunct to two-dimensional (2D) mammographic imaging] [117][118][119][120] . One appeal is the reduction of false-positives (approximately 15%) and increased cancer detection rates (approximately 28%; for invasive cancers, 40% or more) [121][122][123] , together with a onethird reduction in recall rates and consequent false-positive biopsies 117,124,125 , especially in younger women and women with dense breasts in whom mammography is limited, and with no negative effect on sensitivity 123,[126][127][128] , which could potentially tip the risk:benefit ratio toward tomosynthesis 129,130 .…”
Section: New Screening Modalities: Digital Breast Tomosynthesismentioning
confidence: 99%